GAMBARAN SUBJECTIVE WELL-BEING PADA MAHASISWA PROGRAM STUDI PSIKOLOGI UNIVERSITAS X - Karimah, Lina Nikmatul; Musslifah, Anniez Rachmawati (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This research aims to look at the general picture of subjective well-being in terms of cognitive and affective aspects, and the contribution of factors forming subjective well-being to the level of subjective well-being in students of the Psychology study program at University of X. Subjective well-being is explained as an evaluation A person's subjective opinion about their life includes overall satisfaction with life which is characterized by high positive affect and low negative affect (Diener, 1984). The method used in this research is a qualitative method, using semi-structured interviews. The informants in this research were seven students from the Psychology study program at University of X. The results of the research show that of the seven informants it can be concluded that four of them have subjective well-being which is dominant in positive affect and three informants have subjective well-being which is dominant in negative affect. The percentage of informants who felt positive affect and life satisfaction was higher than informants who felt negative affect. Factors that influence subjective well-being in research include self-esteem, self-compassion, meaningfulness of life, social support, and personality. For further research that is interested in conducting research with the same theme, it is hoped that it will deepen the factors that influence subjective well-being in students, such as gender and age. The informants studied also need to have varied backgrounds